Libro fotográfico sobre la historia del Ex Penal García Moreno en Quito. - Suárez Galarza, Cynthia Stefany (2018)
The present work portrays the historical memory of the penitentiary system in the first prison in Ecuador called, "Former Criminal García Moreno" and nicknamed "Crime Museum", in which, it was translated into a photographic book governed by the function of collective memory generated in this place. When the information is collected, this editorial product is created, based on different sources such as: interviews, photographs, texts and documents that helped focus on our main objective, which is to design a photographic book where the historical memory of the Ex García Moreno prison in Quito. The analysis carried out has a research purpose within anecdotes, experiences and experiences, which seeks to show in images the portrait of how they passed year after year the inmates of the prison and in turn, feeling at home because they were several years of condemnation for those who had to pass. The purpose of this product is to reach a society that understands how the system was composed for people deprived of their freedom, and in turn, to identify the main conflicts that took place within this rehabilitation scenario, such as differences social, economic and cultural. Thus, we explain how our academic work is composed and designed, which we present to you in a photographic session of one hundred real images, captured in a photographic book that describes and portrays social rehabilitation in Ecuador.